Production Performance and Sperm Characteristics of Quail (Coturnix-coturnix japonica) with Different Concentrations of Yolk Immunoglobulin - Satri Yusasra Agasi; Niken Ulupi; Rudi Afnan; R. Iis Arifiantini (Indonesian Center for Animal Research and Development (ICARD), 2023)
Quails are classified according to their immunity to different IgY concentrations. Quail IgY concentrations range from 0 to 1200 µg ml-1, and these IgY concentrations may affect production and reproductive performance. This study aimed to analyze IgY concentrations in male quail and to compare production and reproductive performance at different IgY concentrations. Forty-two male quail at five weeks of age participated in the study, including 29 quail with low IgY concentration (210-393 µg ml-1) and, 13 with intermediate IgY concentration (403-564 µg ml-1). The observed productive performances were feed intake, initial body weight, final body weight, weight gain, feed conversion, morbidity, and mortality. In addition, this study observed testicular weight and macroscopic and microscopic semen quality for reproductive traits. Differences in production and reproductive performance of each group were analyzed using an independent-sample t-test. The result showed that male quail with different IgY concentrations were equal in all productive traits (P0.05). This means that male quail with low IgY and medium IgY concentrations are equally good. Testicular weight, semen color and pH were identical at different IgY concentrations. Quails with low IgY concentrations have better sperm consistency, which is related to the weight of the testes, which are heavier in quails with low IgY concentrations than in those with moderate IgY concentrations. This consistency is related to the concentration of sperm in the semen. The result concludes IgY concentrations in male quail did not affect production performance. Quails with low IgY concentration had thicker sperm consistency and higher sperm concentration.